INTEGRASI DATA WEBSITE STUDENTS.BSI.AC.ID UNTUK MOBILE INFOKAMPUS BERBASIS ANDROID MENGGUNAKAN EKSTRAKSI HTML - Agung Sasongko (LPPM Nusa Mandiri, 2017)
This paper study data integration students.bsi.ac.id website for Android using extracting data from the source HTML code. Bina Sarana Informatika is one of the private universities with the number of active students are many and implementing the Academic Information System as a means of information to the entire academic community. In addition to direct access through a browser, access to the system is required alternatively as an effort to reduce the workload of the server. Data integration by mobile becomes alternative access to the server lighter which typically uses RESTful which may improve performance speed and resource savings. Data integration of website that does not have a RESTful then the alternative may use HTML extraction methods. The advantages of this method are: no need to create feature RESTful on the server and can save the bandwidth of the server when requesting content. This study found that the performance of mobile applications infokampus can save the consumption of bandwidth access to a server with average access per page 16.68kB or 91.54% less than access through a browser, but process per page average 1.75 seconds, which is longer 117.68% than a browser that an average of only 0.803 seconds.